Self-compassion in parents of children with chronic illnesses: A concept analysis - Boonlue, Chayapa; Srisawet, Siriluk (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Having a child with a chronic condition presents major stress for parents and can adversely affect parenting quality, thus jeopardizing children’s outcomes. Self-compassion serves as an emotion regulation strategy to cope with stress from parenting, but remains unexplored, particularly in the parents’ context related to their children’s chronic illnesses. Objective: This paper aimed to explore and analyze the concept of self-compassion in parents of children with chronic illnesses to inform future research, clinical practices, and intervention designs for improving parenting outcomes. Methods: Walker and Avant’s eight-step concept analysis approach was conducted, which comprised selecting the concept, defining analysis aims, conducting a literature search (2014–2024) using specified keywords across major databases (CINAHL, ScienceDirect, PubMed, Medline, ProQuest, Scopus and Google Scholar), identifying defining attributes, presenting model, borderline, related, and contrary cases, and outlining antecedents, consequences, and empirical referents. Results: The attributes of self-compassion in parents of children with chronic illnesses consist of self-kindness, common humanity, mindfulness, and motivation to relieve suffering. Antecedents comprise illness perception, social support, and stigma. Consequences are improved parents’ psychological well-being (decreased depression, anxiety, parental stress, and burnout), effective parenting (parental responsiveness and mindful parenting), and reduced children’s difficulties (internalizing and externalizing symptoms). Conclusion: This concept analysis offers the antecedents, attributes, and consequences of self-compassion in parents of children with chronic illnesses. Nursing care should focus on self-compassion education that incorporates interdisciplinary collaboration to enhance parents’ understanding of their child’s illness. Nurses should assess social support, encourage parents to seek support networks, and provide skill training to cope with stigma. Healthcare professionals need training for cultural competence to work with families from diverse cultural backgrounds and manage cultural differences in parenting practices and child-rearing standards.